A new finding of the European mudminnow (Umbra krameri, Walbaum 1792) in Croatia - Jelkić, Dinko (Array, 2019)
Distribution of the European mudminnow, Umbra krameri, Walbaum 1792, in Croatia is scarce with only few confirmed localities. In order to confirm presence of the European mudminnow in amelioration canal network along the Drava River an electrofishing was conducted in the small Mlinski canal. Ten specimen of European mudminnow were caught During sampling. Using ImageJ software a truss network was constructed between landmark points on photographs of caught specimens. Total body lengths of caught European mudminnow ranged from 61 to 100 mm (72.00±11.52 mm) whereas standard one ranged from 52 to 85 mm (60.30±10.08 mm). Body weight were relatively small ranging from 1.81 to 7.59 g (3.80±1.89 g), while the Fulton condition factor ranged from 0.76 to 1.23 (0.96±0.15). This new locality of the European mudminnow is situated about 50 km downstream from the last confirmed site in Croatia.